Emisión de gases de efecto invernadero en la planificación de la generación de energía del Sistema Eléctrico Interconectado del Perú - Sarango, Douglas (2021)
In this investigation, the environmental impact was determined by the use of fuels derived from petroleum, coal and natural gas in the planning of the generation of energy of the National Interconnected Electrical System (SEIN) in the period 2016-2019. The amount of C, CH4, N2O, NOx, CO and NMCOV, emitted into the environment by the use of Diesel 2, Residual 500, Residual 6, Coal and Natural Gas fuels has been quantified. These emissions are depended of fuel type, thermoelectric power plant annual energy generation and other factors of emissions due to burning fuels in the Peru`s Electric Sector obtained for Intergovernmental Panel on Climate Change (IPCC) in 1996. The PERSEO model was used to obtain the optimization planning of the SEIN generation expansion in the period 2016-2019 and it is being used by the Supervisory Agency for Energy and Mining Investment (OSINERGMIN).